The Impact of Listening to, Reciting, or Memorizing the Quran on Physical and Mental Health of Muslims: Evidence From Systematic Review - Wan Nor Atikah Che Wan Mohd Rozali; Ismarulyusda Ishak; Arimi Fitri Mat Ludin; Farah Wahida Ibrahim; Nor Malia Abd Warif; Nur Aishah Che Roos (Frontiers Media S.A., 2022)
Objectives: Listening to or memorizing the Quran has been suggested to affect the psychosocial health and well-being of Muslims. Muslims who memorized Quran have a higher quality of life (QoL) and lower anxiety and stress. Hence, this systematic review was conducted to evaluate the studies that assessed the effect of listening to, reciting, or memorizing the Quran on physical and mental health.Methods: This review was performed on articles published from the inception and April 2021. Databases including ProQuest, PubMed and Web of Science were searched on 19 April 2021. Keywords such as "Quran", "al- Quran," "al- Kareem," "Holy Quran," "memori," "Tahfiz," "Huffaz," "listening" and "reciting" were used for databases searching. The risk of bias was assessed using Cochrane risk of bias tool and Joanna Briggs Institute (JBI). Only 20 articles were included in data synthesis out of a total of 230.Results: The findings revealed that listening to, reciting or memorizing the Quran had a favorable effect on depression, anxiety, physiologic parameters, quality of life, quality of sleep and intelligence quotient.Conclusion: The current evidence suggests that, listening to, reciting or memorizing the Quran may be useful as an intervention to improve physical and mental health.